Identification and Control of a Piezoelectric Bender Actuator - Maslan, Mohd Nazmin (IEEE, 2012)
This paper focuses on determining the transfer function (TF) of a highly nonlinear and hysteretic piezoelectric actuator and its inverse. A system identification (SI) technique was employed based on the direct measurements of the input-output data from a bender type piezoelectric actuator mounted on a suitably designed platform equipped with appropriate instrumentation. Eventually, the actuator TF models were approximated through a rigorous analytical procedure. Verification and validation of the results are performed to ensure that the transfer functions obtained are practically viable and implementable. An illustrative case study is also carried out involving the control of the identified piezo actuator using closed-loop control methods that employ a conventional proportional-integral-derivative (PID) controller and PID with active force control (PIDAFC). The outcome of the study clearly indicates the effectiveness of the proposed schemes.